2016
DOI: 10.1007/s12306-016-0401-8
|View full text |Cite
|
Sign up to set email alerts
|

The influence of subscapularis tendon reattachment on range of motion in reversed shoulder arthroplasty: a clinical study

Abstract: In reverse shoulder arthroplasty, no significant differences on range of motion, functional outcome scores or strength were found between subscapularis repair or no repair, whether the tendon healed at follow-up or not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
80
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(81 citation statements)
references
References 19 publications
0
80
1
Order By: Relevance
“…Only 2 studies in the literature 7,8 have examined whether the patients who underwent subscapularis repair at their index repair had an intact tendon during follow-up examination, and both of these studies used a reverse shoulder implant that has an onlay metaphysis and 145 to 155 neck shaft angle. A study by de Boer et al 7 examined integrity of repair with ultrasound in 25 patients who underwent repair after a tenotomy with tendon-tendon and tendon-bone suture fixation and found that 10 of the 25 (40%) were intact, with no difference in clinical outcome 8 examined 48 shoulders that underwent RTSA with subscapularis repair with transosseous sutures after a lesser tuberosity osteotomy and tenotomy. Ultrasound evaluation of these patients demonstrated that 23% of the subscapularis tendons were not healed at evaluation, 13% were intact, 33% were attenuated, and 31% were severely attenuated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 2 studies in the literature 7,8 have examined whether the patients who underwent subscapularis repair at their index repair had an intact tendon during follow-up examination, and both of these studies used a reverse shoulder implant that has an onlay metaphysis and 145 to 155 neck shaft angle. A study by de Boer et al 7 examined integrity of repair with ultrasound in 25 patients who underwent repair after a tenotomy with tendon-tendon and tendon-bone suture fixation and found that 10 of the 25 (40%) were intact, with no difference in clinical outcome 8 examined 48 shoulders that underwent RTSA with subscapularis repair with transosseous sutures after a lesser tuberosity osteotomy and tenotomy. Ultrasound evaluation of these patients demonstrated that 23% of the subscapularis tendons were not healed at evaluation, 13% were intact, 33% were attenuated, and 31% were severely attenuated.…”
Section: Discussionmentioning
confidence: 99%
“…When the decision to repair the subscapularis is made, very little is known regarding optimal repair technique and outcomes after repair based on repair integrity, as only 2 studies to date in the literature have examined subscapularis repair integrity postoperatively. 7,8 Stem-based repair of the subscapularis has shown promising biomechanical sonographic and clinical results in anatomic total shoulder arthroplasty. 15,16 A similar technique has been developed for reverse shoulder arthroplasty.…”
mentioning
confidence: 99%
“… 25 Or the study by de Boer et al which evaluated the influence of the subscapularis tendon on the ROM in rTSA, which included 65 patients. 14 …”
Section: Methods and Analysismentioning
confidence: 99%
“…Also, de Boer et al showed no significant differences in a range of motion (ROM) between subscapularis tendon repair or resection. 14 Without the need to reattach the subscapularis tendon, combined with the stability provided by the modern design of rTSA, patients can start mobilisation directly postoperative. In the study by Denard et al , patients undergoing anatomic total shoulder arthroplasty showed an increased ROM in the first 3 months in patients who were not immobilisated postoperatively compared with usual care.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, those 2 investigations 13 , 24 remain the only studies that have specifically examined the role of subscapularis repair on dislocation. One recent study 31 demonstrated no difference in functional or patient-reported outcomes after treatment with a medialized design with or without subscapularis repair, yet little work has been done to evaluate the effect of subscapularis repair on outcomes after reverse shoulder arthroplasty with a lateralized prosthesis, to our knowledge. Therefore, the present study was designed to further clarify the rates of complications, including dislocation, after lateralized reverse shoulder arthroplasty and to compare the functional outcomes after reverse shoulder arthroplasty performed with a lateralized design with or without subscapularis repair.…”
mentioning
confidence: 99%